Synthesis and properties of oligochitosan ascorbate from Bombyx mori - Pirniyazov, K.K.; Tikhonov, V.E.; Rashidova, S.Sh. (KU Publ., 2021)
Oligochitosan samples were obtained by acid hydrolysis of high molecular weight chitosan isolated from Bombyx mori (B.M.). Carrying out acid hydrolysis for 6 hours, it was found that after 4 hours and further with increasing duration, the molecular weight of chitosan decreases to a value corresponding to the ranges of molecular weights of oligochitosan 2–16 kDa. It has been seen that the optimal duration of hydrolysis, leading to the production of oligochitosan with a molecular weight of less than 16 kDa, should be considered 4–5 hours. Depolymerization of chitosan with a molecular weight of 177 kDa was carried out using sodium nitrite in solution to obtain oligochitosan with a molecular weight of 6 kDa. On the basis of oligochitosan samples obtained by two methods, their ascorbates were received. Under constant conditions with varying the ratio of the components (ChS:AA) and the pH of the solution, the reaction of chitosan ascorbate formation was carried out on the basis of the suspension method. The composition, structure, and molecular weight characteristics of oligochitosan ascorbate and oligochitosan Bombyx mori samples were confirmed by physicochemical methods. It has been seen that the obtained samples have antimicrobial properties against Fuzarium oxysporum.
Bombyx mori-ден алынған олигохитозан аскорбатының синтезі және қасиеттері
Синтез и свойства аскорбат олигохитозана из Bombyx mori
Keywords: Bombyx mori chitosan ascorbate; Bombyx mori oligochitosan; ascorbic acid; donor-acceptor bond; degree of binding; degrees of acetylation; depolymerization